PENGUATAN PEMASARAN PRODUK BATIK TULIS “MBAH JO” MELALUI STRATEGI PRODUCT BRANDING - Andri Wahyu Utomo; Shelly Merlyana Putri Meylani, Siska Lutfi Emiliana, Aulia Permatasari (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The "Mbah Jo" Batik micro, small and medium enterprise (UMKM) industry is a batik industry that was established in 2011 in Kenongorejo Pilangkenceng Madiun Village. In carrying out marketing activities, Bataik Tulis businesses use a conventional system, so this study aims to optimize innovative, effective and efficient marketing strategies through the use of digital marketing as an effort to maximize selling power. KKN-T 56 and this study used a qualitative method by going through the stages of a survey of business actors. During the implementation, mentoring and training was carried out by optimizing facilities on social media such as Facebook, Instagram, Youtube and Whats AppBusiness which can be accessed via smartphones. The expected output of this research can produce more innovative, effective and efficient strategies. So that it can attract consumers and business people to know the positive impact on optimal use of social media in the business sector